Determinación de los Índices Reproductivos de cuyes mejorados (Cavia porcellus) alimentados con Forrajes Hidropónicos a base de Maíz (Zea mays) y Arroz (Oryza sativa) en el trópico - Nuñez Acosta, Gabriela Cristina (2024)
The present research was developed in the Minor Species Production Program of the Technical University of Babahoyo – Ecuador, where the effect of Hydroponic Forages based on Corn (Zea mays) and Rice (Oryza sativa) on the Reproductive Indices of guinea pigs was evaluated. improved (Cavia porcellus) for 14 weeks, 45 animals were used, 36 females and 12 males, 70 days old in the reproductive stage, distributed in three treatments T1 (Alfalfa + Concentrate + Water ad libitun) T2 (Hydroponic Forages based on Corn ( Zea mays) + Concentrate + Water ad libitum) and T3 (Hydroponic Forage based on Rice (Oryza sativa) + Water ad libitum) (with three repetitions and 5 experimental units each; Reproductive Behavior was evaluated by establishing as variables: Percentage of pregnancy, Litter size, Average litter weight at birth, Average litter weight at Weaning and Mortality at first birth per treatment, Postpartum estrus and the Cost Benefit Indicator, the treatments were distributed under a Completely Randomized Design (DCA). ), where the experimental results obtained were subjected to an Analysis of Variance for the differences (ANDEVA), and Mean Separation according to Tukey at the significance levels of (P ≤ 0.05 and P ≤ 0.01)., with T2 the best results were achieved. results for the variables pregnancy percentage 100%; Litter size 4 – 6 pups per litter; Average weight of the litter at birth was 122.25g, a favorable indicator; average weight of the litter at weaning greater than 1000 grams which shows a weight gain that was 295.52g in this period of time and a Benefit/Cost of 2.57 resulting in a sustainable and profitable diet in this type of productions